Carbon Footprint of the Coffee Roasting Process Based on Two Technologies with Different Sources of Energy in Peru - Karin Bartl, María de los Ángeles Franco (European Journal of Sustainable Development, 2018)
The objective of this study was to determine and to compare the Carbon Footprint (CF) of the coffee roasting process carried out by using two technologies with different sources of energy. To this aim, two coffee roasting companies were selected in the rainforest of Peru. These companies apply concentrated solar and photovoltaic energy, and electricity from the local grid as source of energy during the coffee roasting process. For this determination, primary data was collected from the two companies located in the province of Satipo, Junin, Peru. The information obtained was analyzed according to the procedures and requirements of ISO 14040 (Life Cycle Analysis) to obtain the carbon footprint, and then processed with the software "SimaPro" to evaluate the environmental impacts due to the effect of climate change. The results indicated a CF of the solar energy roasting process of 0.318 and a CF of the local electricity grid production of 0.744 kg CO2-eq per kg of roasted coffee. This represents a difference in greenhouse gases (GHG) emissions of 134%. Within the factory activities, the stage with the highest environmental impact or "hotspot" was the roasting stage, where the most sophisticated machines are used and generated emissions from the combustion of fossil fuels. From this, proposals and recommendations to improve the strategies include an approach to clean technologies for a sustainable development in the sector, among others. Keywords: LCA, Carbon Footprint, Roasted Coffee, Renewable Energy, Photovoltaics, Concentrated Solar Energy